Determinants of cross-border acquisitions in the EU - Wildmer Daniel Gregori; Maria Martinez Cillero (Argomenti: Rivista di Economia, Cultura e Ricerca Sociale, 2021)
This study empirically investigates the determinants of the probability that a European Union firm received and completed a takeover bid. Our identification strategy relies on the logit method-ology, using cross-border acquisitions and firm level balance sheet data for the years 2008-2018. We find that higher productivity in-creases the probability of acquisition, except for large firms. Higher firm liquidity, and listing status also increase the probability of a cross-border acquisition. On the other hand, age, profitability, higher indebtedness and equity levels are negatively related to the probability of acquisition. Some sectoral variation, dividing high vs low tech sectors, is also observed in our estimates.